Touraine-Solente-Gole syndrome: pathogenic variant in SLCO2A1 presented with polyarthralgia and digital clubbing - Rafaela Nicolau; Tiago Beirão; Francisca Guimarães; Francisca Aguiar; Sara Ganhão; Mariana Rodrigues; Ana Grangeia; Iva Brito (BMC, 2023)
Abstract Background Primary Hypertrophic Osteoarthropathy (PHO), also known as Touraine-Solente-Gole Syndrome, is a rare, multisystemic autosomal recessive disorder caused by pathogenic variants in the 15-hydroxyprostaglandin dehydrogenase (HPGD) or Solute Carrier Organic Anion Transporter Family Member 2A1 (SLCO2A1) genes. However, autosomal dominant transmission has also been described in some families with incomplete penetrance. PHO usually starts in childhood or adolescence, presenting with digital clubbing, osteoarthropathy, and pachydermia. We described a complete form of the syndrome in a male patient with a homozygous variant in the SLCO2A1 gene (c.1259G > T). Case presentation A 20-year-old male was referred to our Pediatric Rheumatology Clinic with a five-year history of painful and swollen hands, knees, ankles and feet, prolonged morning stiffness and relief with non-steroidal antiinflammatory drugs. He also reported late onset facial acne and palmoplantar hyperhidrosis. Family history was irrelevant and parents were non-consanguineous. On clinical examination, he presented clubbing of the fingers and toes, moderate acne and marked facial skin thickening with prominent scalp folds. He had hand, knee, ankles and feet swelling. Laboratory investigations showed elevated inflammatory markers. Complete blood count, renal and hepatic function, bone biochemistry were normal, as well as immunological panel. Plain radiographs revealed soft tissue swelling, periosteal ossification and cortical thickening of the skull, phalanges, femur and toe acroosteolysis. Due to the absence of other clinical signs suggesting a secondary cause, we suspected PHO. A genetic study revealed a likely pathogenic variant, c.1259G > T(p.Cys420Phe), in homozygosity in the SLCO2A1 gene, thus confirming the diagnosis. The patient started oral naproxen with significant clinical improvement. Conclusions PHO should be kept in the differential diagnosis of inflammatory arthritis affecting children, often misdiagnosed as Juvenile Idiopathic Arthritis (JIA). To the best of our knowledge, this is the second genetically confirmed case of PHO in a Portuguese patient (first variant c.644 C > T), both made at our department.